Beneficial Effect of Treatment for Strabismus in Patients with Bilaterally Poor Vision, Who Cannot See Their Strabismus. (8th March 2013) - Dawson, Emma L. M.; Leung, Harry; Webster, Andrew; Lee, John P.
ABSTRACT: Methods: Retrospective case note review of management of patients with bilaterally severely reduced vision presenting with symptomatic strabismus. Results: There were 10 females and 7 males, mean age at treatment was 36 years, range 19 to 74 years. Thirteen patients had an exotropia ranging from 20 to 90 Δ (mean 52 Δ ). Four had an esotropia ranging from 30 to 70 Δ (mean 53 Δ ). Vision in each eye ranged from 6/24 Snellen to light perception, except for one patient with Usher's syndrome who had grossly restricted visual fields and vision of 6/12 and 6/36. The etiology was retinitis pigmentosa in 5 patients; 3 had cone dystrophy, 2 were high myopes. Other etiologies included CMV retinitis in both eyes secondary to HIV, bilateral optic atrophy post craniopharyngioma, and cortical visual impairment. All patients were unable to see well enough to assess their strabismus but were aware of its presence from family members and friends and wished improvement. Eleven patients underwent botulinum toxin injections; 2 of these then proceeded to surgery. A total of 8 patients had surgery. Post-operative angles ranged from 6 Δ to 25 Δ of esotropia. Five patients continue with maintenance toxin. Follow-up ranged from 3 months to 15 years. Discussion/Conclusions: This is the first report of patients with bilaterally severely reduced vision requesting treatment for strabismus that they were unable to see for themselves. All patients were pleased they had undergone treatment for their strabismus despite being unable to see the outcome.